ผลของการจัดกิจกรรมการเรียนรู้แบบ SSCS เพื่อส่งเสริมความสามารถในการแก้ปัญหา ทางคณิตศาสตร์ และผลสัมฤทธิ์ทางการเรียนวิชาคณิตศาสตร์ ของนักเรียนชั้นมัธยมศึกษาปีที่ 3 - เกษี, จีราวะดี (Journal of Graduate School Sakon Nakhon Rajabhat University, 2018)
The purposes of this study were 1) to develop SSCS activities on the topic of “Surface area and Volume” for Mathayomsuksa 3 students based on the 75/75 criterion, 2) to find out the effectiveness index of the SSCS activities versus the regular learning activities on the topic of surface area and volume for Mathatayomsuksa 3 students and, 3) to compare the ability to solve mathematical problems and the learning achievement on the topic of surface area and volume of the students treated with the SSCS activities and of those who were taught in a normal class. The samples of the study, selected through cluster random sampling, were Mathayomsuksa 3 students from two different classes at Don Chan Witthayakhom School, Don Chan District, Kalasin Province during the first semester of the academic year 2015. Then, the two classes were designated by means of the simple random sampling technique as Experimental Group 1 with 30 students and Experiment Group 2 with 28 students. The intervention lasted 19 periods, each covering 50 minutes. The four types of the research tools employed included: the SSCS learning plan versus the normal learning plan--each composed of 15 plans; an achievement test on the mathematics subject under the topic of surface area and volume, which was a multiple choice test containing 20 items with 4 answers to select; and a 5-item test to determine the student’s ability to solve mathematical problems. The statistics used included mean, percentage and standard deviation. The hypotheses were tested by means of Hotelling’s T2. The study results were as follows: 1. The effectiveness (E1/E2) of the SSCS lesson plan was 86.00/86.50 and that of the regular lesson plan was 77.01/77.33, which were higher than the established criterion of 75/75. 2. The SSCS lesson plan had the effectiveness index of 0.7065, indicating the students’ progress at 70.65%. Meanwhile, the effectiveness index of the normal lesson plan was 0.6631, indicating that the students’ progress was merely 63.31%. 3. The students involved in the SSCS activities had more ability to solve mathematical problems as well as higher learning achievement than those learning in a normal class, at the significance level of .05.